Community Outreach Awareness, Involvement, Motivation, and Challenges in a Philippine Catholic Higher Education Institution - Calimpos, Elmeer Meeynard; Verdeprado-Mangga, Richelle; Madrigal, Dennis (Technium Social Sciences Journal, 2023)
Community outreach serves as a core function of higher education institutions which helps promote sustainable development goals worldwide. In the Philippines, universities have been mandated to provide extension activities and reach the most vulnerable communities in the country. Thus, the study used descriptive, comparative, and correlational approaches to determine the level of awareness, the extent of involvement, the degree of motivation, and the challenges in community outreach in a Catholic Higher Education Institution in the areas of spiritual-moral, education, sociocultural, health, economic, and environment. Using stratified random sampling, 459 students, faculty, and administrators participated in the study through a modified-standardized instrument. Mean, standard deviation, frequency, percentage distribution, Kruskal Wallis, and Spearman rank were used to analyze the data. The findings of the study unveiled that the respondents of the university have a very high level of awareness, a moderate extent of involvement, and a very high degree of motivation. The topmost challenge is time constraints. This signifies that members of the academic units are generally very aware of and highly motivated in community outreach, but involvement has yet to be enhanced. Findings suggest revisiting the community outreach plan and enriching its strategies to attain a more inclusive and progressive involvement among university stakeholders.